Sistem Pengupahan dan Program Insentif Terhadap Produktivitas Karyawan Pada PT Wijaya Bangun Pertiwi: Wage System and Incentive Program for Employee Productivity at PT Wijaya Bangun Pertiwi - Niken Pratiwi (CV Warnak Johanna Nusantara, 2024)
PT Wijaya Bangun Pertiwi is a company engaged in subcontracting painting work. The wage system and incentive programs are factors that strengthen each other for the company's progress, because if the wage system and incentive programs in the company cannot meet the needs of employees, it will certainly affect employee productivity. The purpose of this study is to find out the Influence of the Wage System and Incentive Program on Employee Productivity at PT Wijaya Bangun Pertiwi. The type of data used is quantitative research using the multiple linear regression data analysis method processed using the SPSS version 20 program. The sampling technique used is Non-Probability Sampling using a purposive sampling sample of 30 respondents. The data sources used are primary data such as observation and distributing questionnaires. While the secondary data is a documentation study. The results of this study prove that the Wage System has a calculated value of 2.353 > a table of 1.701 with a significance value of 0.026 < 0.05, partially the wage system has a significant and positive effect on employee productivity, the Incentive Program has a calculated value of -2.630 > a table of 1.701 with a significance value of 0.014 < 0.05 partially, the incentive program has a significant and negative effect on employee productivity and the Wage System and Incentive Program Fcalung 3,469 > Ftable 3,350 with a significance value of 0.046 < 0.05 simultaneously have a significant and positive effect on employee productivity.